SHARI'A SUPERVISORY BOARD AND ISLAMIC BANKS’ INSOLVENCY RISK - Umar, Umar Habibu; Abduh, Muhamad; Besar, Mohd Hairul Azrin (Bank Indonesia, 2023)
This study examines how the characteristics and quality of Shari'a supervisory board (SSB) influence the insolvency risk of Islamic banks. It employs unbalanced panel data of 43 Islamic banks in 15 countries between 2010 and 2020, which are hand-collected from the banks’ annual reports. The results indicate that the SSB quality index, SSB Islamic finance professional expertise and SSB competency increase insolvency risk while the SSB members with PhDs reduce it. Meanwhile, SSB size, SSB meetings, SSB gender diversity (SSBG) and SSB members from foreign countries have no significant influence on the insolvency risk. These findings have implications for policymakers and regulators in carving policies and regulations in restraining the SSB from taking excessive risk. They can also guide the Islamic banks' board of directors and shareholders in appointing the SSB members. Acknowledgment The authors are grateful to the Bank Indonesia Institute and Bank Indonesia for the honorarium given after the publication.